Explaining the Energy-Saving Behavioral Intention of Workers in Industrial Zones - Dung, La Nguyen Thuy; Nguyen, Quoc Nghi; Hien, Le Thi Dieu (International Journal of Energy Economics and Policy, 2024)
The objective of this study is to demonstrate the factors influencing the energy-saving behavioral intention of workers employed in industrial zones in Vietnam. The study applies the extended Theory of Planned Behavior (TPB) to explain the energy-saving behavioral intention of workers. Convenience sampling was used to collect data, with an official sample size of 454 workers. The research process includes six steps, combining both qualitative and quantitative research. The research results indicate that the energy-saving intention of workers in industrial zones is positively influenced by factors such as attitude, perceived behavioral control, personal moral norms, injunctive norms, descriptive norms, and perceived benefits. Among these, the attitude factor was evaluated as having the strongest impact on energy-saving intention. The study proposes several managerial implications to enhance the energy-saving intention of workers in industrial zones.